THE EFFECT OF PAPAYA DERIVED EXOSOME-LIKE NANOPARTICLE TO INHIBIT PHOTOAGING IN 1BR3 FIBROBLAST CELL LINE AND ZEBRAFISH (DANIO RERIO) - Nasharo Qisthia Farid, Faticha
Indonesia, as a tropical nation, experiences consistent year-round ultraviolet (UV) radiation exposure. Excessive ultraviolet radiation (UVR), particularly ultraviolet B (UVB), accelerates premature skin aging, known as photoaging. UVB radiation induces photoaging by directly damaging DNA and increasing the production of reactive oxygen species (ROS), which leads to oxidative stress and results in increased apoptosis, melanogenesis, senescence, cell cycle arrest, and reduced cell migration capacity.. Thus, identifying agents that can mitigate photoaging is crucial for developing skincare therapies. One of the alternative therapies currently being developed in dermatology is the application of plant-derived exosome-like nanoparticles (PDEN). Papaya (Carica papaya), renowned for its flavonoid and phenolic content, exhibits potent antioxidant properties and has been extensively utilized in skincare formulations. Therefore, this study investigates the effects of papaya derived exosome-like nanoparticles (CP-PDEN) on inhibiting photoaging in 1BR3 fibroblast cell lines and zebrafish. CP-PDEN isolation was performed through filtration, gradient centrifugation, and precipitation using PEG6000. Characterization of CP-PDEN size and morphology was performed using particle size analyzer (PSA) and transmission electron microscopy (TEM), while concentrations were measured via bicinchoninic acid (BCA) assay. CP-PDEN internalization into 1BR3 fibroblast cell lines was evaluated using PKH67 fluorescence labeling. UVB-induced photoaging was simulated using 100 mJ/cm² exposure for 15 minutes. Functional assays included MTT assay for cytotoxicity evaluation, DAPI staining for nuclear morphology evaluation, and scratch assays for cell migration evaluation. An in vivo zebrafish model was employed to assess anti-melanogenesis effects, with 1-phenyl 2-thiourea (PTU) as a positive control. Results indicated that CP-PDEN were spherical with an average size of 135.4 ± 0.15 nm and a zeta potential of -17.03 ± 0.2 mV., effectively internalized into 1BR3 cells within one hour. Cytotoxicity assays revealed that CP-PDENs were non-toxic up to 5 ?g/mL, maintaining >90% cell viability. Post-UVB exposure viability tests showed that 2.5 ?g/mL CP-PDEN significantly increased 1BR3 cell viability. Nuclear morphology observations of 1BR3 cells showed that PDEN treatments at 2.5 ?g/mL and 5 ?g/mL inhibited cellular senescence. Scratch assay showed that PDEN treatment at 2.5 ?g/mL improved cell migration. In vivo studies with zebrafish also showed that PDEN treatment at a concentration of 2.5 ?g/mL reduced melanogenesis activity. Collectively, these results suggest that CP-PDEN has a protective effect against photoaging in the 1BR3 fibroblast cell line and zebrafish.